Early Detection Of Secondary Hypertension: Collaborative Screening Framework In Primary Health Care Settings Role Of Family Physicians And Nursing (The Review of Diabetic Studies, 2024)
Secondary hypertension is a significant public health concern, accounting for a notable percentage of hypertension cases in the population. It stems from identifiable medical conditions such as endocrine disorders, renal diseases, or certain medication effects. Therefore, prompt and accurate diagnosis is crucial to prevent severe health consequences, including cardiovascular complications, stroke, and renal failure. Family physicians and nursing personnel play critical roles in the early detection and management of secondary hypertension in primary health care settings. This paper outlines the pivotal roles of family physicians and nursing staff in identifying, evaluating, and managing secondary hypertension, emphasizing the importance of a collaborative screening framework that enhances early detection and leads to improved patient outcomes. The integration of evidence-based protocols, effective communication strategies, and patient-centered care is vital for optimizing care delivery in primary care settings.